Ilmastonmuutoksen hidastamiskeinot maataloussektorilla ja niiden sosioekonomisten vaikutusten arviointi - Sinkkonen, Marko (MTT, 2001)
This report acts as a feasibility study in order to compile and sum up facts on climate change in an agricultural context and to find out possible mitigation strategies for greenhouse gas emissions from agriculture. This report provides a basis for a later study on alternative ways to cut greenhouse gas emissions. Accuracy of emission parameters presented by International Panel of Climate Change (IPCC) is also discussed from the Finnish emission calculation viewpoint. This study is the first part of the project Socio-economic impacts of mitigation of greenhouse gas emissions from agriculture running in MTT Economic research. This study will be used in determining the work further in the project. Cutting down emissions from animal production is excluded from the project. This study pinpoints three main possibilities to affect greenhouse gas emissions from Finnish agriculture: 1. to modify or cease some currently used cultivation practices in organic soils; 2. to reduce nitrogen fertilisation; 3. to modify land allocation to different plants according to their emissions. Some other interesting alternatives are also discussed, but their analysis will be saved for further work. After this feasibility study the project as a whole will go deeper in studying alternative ways to cut emissions from agriculture and assess social, ecological and economical impacts caused by suggested actions. This feasibility study provides information and parameters which will be used as a basis for calculations in future work on the project. A brief discussion on impact assessment in general level is also included.
Keywords: Ma; Ys; vaikutusarviointi; päästöjen vähentäminen; maatalous; ilmastonmuutokset; kasvihuoneilmiö; agriculture; climate change; greenhouse effect; impact assessment; mitigation